DISTRIBUSI KONYAL (Passiflora suberosa L.) DI KEBUN RAYA BOGOR, JAWA BARAT - Althoriq, Luthfi; Hariri, Muhammad Rifqi; Turhadi, Turhadi (Biospecies, 2026)
Konyal (Passiflora suberosa L.) is a wild and invasive plant belonging to the Passifloraceae. The existence of P. suberosa as an invasive species can threaten the existence of local plants. As a scientific conservation area, the Kebun Raya Bogor (KRB) is a habitat for Konyal. One effort that can be made to minimize the threat of invasive species is through mapping. The aim of this research was to map the distribution of konyal (P. suberosa) in the scientific conservation area of Kebun Raya Bogor and measure environmental factors in the habitat of konyal (P. suberosa). The research was carried out using an exploratory method throughout the Kebun Raya Bogor area in January 2024. Documentation of komyal (P. suberosa) and measurements of environmental factors in its growing habitat were carried out during exploring activities. In addition, distribution coordinate data was recorded and used for mapping using QGIS v3.36.2 program. The research results showed that the konyal  (P. suberosa) in the KRB was spread over six areas, including II A, II C, II D, II F, III I, and  XIII A. Environmental factors at the location where P. suberosa was found in the Kebur Raya Bogor area, such as air humidity (70 – 77%), temperature (26 – 33 ˚C), and light intensity (2250 – 16200 lux). Distribution of konyal (P. suberosa) in KRB area showed high density in vak II (II A, II C, II D, and II F). The location vak II has vegetation with sparse canopy and low shade, thereby increasing the sunlight intensity compared to other areas.